Memorandum of Understanding between the James P. Grant School of Public Health, BRAC University, Dhaka, Bangladesh and University of Amsterdam, Amsterdam, The Netherlands (2008) - James P. Grant School of Public Health, BRAC University; University of Amsterdam, Amsterdam (James P. Grant School of Public Health and University of Amsterdam, 2013)
1. Premise. 2. Undertakings. 3. Responsibility of JPG-SPH-BU. and University of Amsterdam. 4. Implementation period of the action. 5. Financing the action. 6. Narrative and financial reporting and payment arrangements. 7. Financial reporting and payment. 8. Validity of the MOU. 9. Governing the validity, construction and performance of the MOU.